Work Systems on LIDAR Laser Sensor - I Wayan Krisna Eka Putra (Media Komunikasi Geografi, 2016)
LIDAR system is a combination of LRF (Laser Range Finder), POS (Positioning and Orientation System) integrated with DGPS (Differential Global Positioning System), IMU (Inertial Measurement Unit) and Control Unit. The working principle of LIDAR systems in general is the sensor emits a laser beam to a target on the surface of the earth, then the laser beam is reflected back to the sensor. Returning beam is then analyzed to determine the distance from the sensor to the object's position and generate 3-dimensional position through the data position and orientation of the sensor. The working principle of laser sensors for distance measurement sensor to the surface of the soil using a different principle or by calculating the distance based interval information required laser light to travel from the transmitter, up to the receiver. At the time of laser sensors scanning process, starting from firing the laser transmitter, then directed by mirrors that move in accordance with the specifications corner were determined. The combination of the work of the components of the laser sensor will provide data to determine the distance from the sensor to the object. Keywords: LIDAR, Laser Sensor, Position 3 Dimensions